Hypoxic ischemic encephalopathy with sensory neural hearing loss as a complication: A 24-month follow up after the initiation of hypothermia therapy - Melda Melda; Endy P. Prawirohartono (Indonesian Pediatric Society, 2022)
Perinatal asphyxia is one of the most common causes of newborn mortality, with an incidence of two to five cases per 1,000 live births in developed countries and tenfold in developing countries.1,2 Lack of oxygen at birth may cause hypoxic ischemic encephalopathy (HIE) with severe neurological consequences, such as cerebral palsy, global developmental delay, blindness or visual defects, hearing loss or deafness, and other comorbidities. Hypothermia therapy is currently the only management option for HIE included in neonatal intensive care unit (NICU) protocols.3 We report here a 24-month follow up of a full-term infant with moderate HIE who underwent hypothermia therapy for 72 hours. The patient had moderate sensorineural hearing loss (SNHL) at her first brainstem evoked response audiometry (BERA) examination at 5 months of age, but had normal hearing and neurodevelopment after 24 months of follow-up.